Acute Postoperative Pain Due to Dental Extraction in the Adult Population: A Systematic Review and Network Meta-analysis. (April 2023) - Miroshnychenko, A.; Ibrahim, S.; Azab, M.; Roldan, Y.; Martinez, J.P.D.; Tamilselvan, D.; He, L.; Little, J.W.; Urquhart, O.; Tampi, M.; Polk, D.E.; Moore, P.A.; et al.
This study compares the effectiveness of pharmacological treatments to develop guidelines for the management of acute pain after tooth extraction. We searched Medline, EMBASE, CENTRAL, and US Clinical Trials registry on November 21, 2020. We included randomized clinical trials (RCTs) of participants undergoing dental extractions comparing 10 interventions, including acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and combinations to placebo. After duplicate screening and data abstraction, we conducted a frequentist network meta-analysis for each outcome at 6 h (i.e., pain relief, total pain relief [TOTPAR], summed pain intensity difference [SPID], global efficacy rating, rescue analgesia, and adverse effects). We assessed the risk of bias using a modified Cochrane RoB 2.0 tool and the certainty of evidence using the Grading of Recommendations, Assessment, Development, and Evaluation approach. We implemented the analyses in RStudio version 3.5.3 and classified interventions from most to least beneficial or harmful. We included 82 RCTs. Fifty-six RCTs enrolling 9, 095 participants found moderate- and high-certainty evidence that ibuprofen 200 to 400 mg plus acetaminophen 500 to 1, 000 mg (mean difference compared to placebo [MDp], 1.68; 95% confidence interval [CI], 1.06–2.31), acetaminophen 650 mg plus oxycodone 10 mg (MDp, 1.19; 95% CI, 0.85–1.54), ibuprofen 400 mg (MDp, 1.31; 95% CI, 1.17–1.45), and naproxen 400–440 mg (MDp, 1.44; 95% CI, 1.07–1.80) were most effective for pain relief on a 0 to 4 scale. Oxycodone 5 mg, codeine 60 mg, and tramadol 37.5 mg plus acetaminophen 325 mg were no better than placebo. The results for TOTPAR, SPID, global efficacy rating, and rescue analgesia were similar. Based on low- and very low-certainty evidence, most interventions were classified as no more harmful than placebo for most adverse effects. Based on moderate- and high-certainty evidence, NSAIDs with or without acetaminophen result in better pain-related outcomes than opioids with or without acetaminophen (except acetaminophen 650 mg plus oxycodone 10 mg) or placebo.